2015
DOI: 10.1111/vox.12291
|View full text |Cite
|
Sign up to set email alerts
|

Automated isolation of primary antigen‐specific T cells from donor lymphocyte concentrates: results of a feasibility exercise

Abstract: The CCS protocol on Prodigy is unrestrictedly functional. It runs fully automatically beyond set-up and thus markedly reduces labour. The quality of the products generated is similar to products generated with CliniMACS Plus. The automatic system is thus suitable for routine clinical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 20 publications
4
17
0
2
Order By: Relevance
“…Other investigators have also validated the feasibility of clinical-scale CMVspecific T-cell selection using the CliniMACS Prodigy [18,20,21]. However, full characterization of the final product has been insufficient due to the limited numbers of isolated cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other investigators have also validated the feasibility of clinical-scale CMVspecific T-cell selection using the CliniMACS Prodigy [18,20,21]. However, full characterization of the final product has been insufficient due to the limited numbers of isolated cells.…”
Section: Discussionmentioning
confidence: 99%
“…The principle of the CCS has been described previously [19], and the CCS process using the CliniMACS Prodigy has also been described recently by Bunos and colleagues [18,20,21]. Briefly, PBS/EDTA buffer and elution buffer were first prepared by adding 0.5% and 2.5% HSA (w/v), respectively.…”
Section: Isolation Of CMV Pp65-specific T Cells Using the Clinimacs Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Such techniques are time-consuming and costly and are very difficult to perform under true Good Manufacturing Practice conditions [29]. In contrast, multimer-based [30] or interferon-g catch [7,31] direct selection of CMV-specific T cells from seropositive donors allows a more rapid production of a cellular product. We demonstrated that a single stimulation with a CMVpp65 peptide pool at day 0 of the expansion period suffices to increase the frequency of CMV-specific cytotoxic cells within CIK cells from CMV-seropositive donors.…”
Section: Discussionmentioning
confidence: 99%
“…Various culture vessels, including G-Rex flasks (Wilson Wolf Manufacturing), cell differentiation bags and bioreactors have proven suitability for T-cell manufacturing [5][6][7]. Current procedures involve a variety of hands-on steps and transfer of cells between cultivation vessels, each bearing the risk of contamination, human errors and cell loss.To simplify the protocol and minimize potential risks during the process, the CliniMACS Prodigy [8] has been adapted to automate clinical-scale manufacturing of cell products [9][10][11]. This platform allows for magnetic beadbased cell separation followed by activation, transduction, multiple media-exchanges and washing steps with a single-use, closed tubing system ( Figure 1A, Figure 1B).…”
Section: Introductionmentioning
confidence: 99%